FACTORS INFLUENCING PURCHASE INTENTION OF FRENCH FRIES 2000 - Wijaya, Nicolas Pratama; Andrew, Richard (Graduate Program of Universitas Tarumanagara, 2025)
PT. Siantar Top, Tbk., the company of nationwide product, French Fries 2000, is currently navigating significant challenges in its sales performance, with a reported decline of 3.33% compared to the previous year. Specifically, sales have decreased from Rp4.931.554.000,00 to Rp4.767.207.000,00. This downturn is primarily attributed to a reduction in consumer purchase intention, which appears to be influenced by several critical factors. Among these are product quality, which can affects consumer trust in a brand or company; product availability, which can limit purchasing opportunities on the product; and product safety, as consumers increasingly prioritize health and safety in their purchasing behavior due to the new normal established by Corona viruses. The objective of this study was to examine the influence of product quality, availability of product, and safety of product on intention to purchase French Fries 2000 products. The population in this study consists of 100 consumers who are aware of, have personally purchased, and have consumed French Fries 2000 products in the Jabodetabek area. The convenience sampling method was used by distributing questionnaires both directly and online through Google Forms media which were then analyzed using PLS-SEM. The findings of this study indicate that product quality can affect purchase intention in French Fries 2000 products, product availability can affect purchase intention in French Fries 2000 products and product safety can affect purchase intention in French Fries 2000 products.